Marginal ice zone fraction benchmarks sea ice and climate model skill - Christopher Horvat (Nature Portfolio, 2021)
Climate models struggle to track the response of Arctic sea ice to warming, leading to efforts to improve sea-ice models. Here the author shows standard model metrics are poor judges of the impact of model improvements, but a new one, marginal ice zone fraction, is optimally suited to this task.